microRNA-493 inhibits tongue squamous cell carcinoma oncogenicity via directly targeting HMGA2 - Jiao D (OncoTargets and Therapy, 2019)
Dan Jiao,1 Yingying Liu,2 Zhen Tian31Department of Ultrasound, China-Japan Union Hospital, Jilin University, Changchun 130033, People’s Republic of China; 2Department of Nephrology, China-Japan Union Hospital, Jilin University, Changchun 130033, People’s Republic of China; 3Department of Cardiology, China-Japan Union Hospital, Jilin University, Changchun 130033, People’s Republic of ChinaCorrespondence: Zhen TianDepartment of Cardiology, China-Japan Union Hospital, Jilin University, No.126 Xiantai Road, Changchun, Jilin 130033, People’s Republic of ChinaEmail Jilin_tianzhen@163.comBackgrounds: microRNA-493-3p (miR-493) has been reported to be critically downregulated in multiple types of human cancer. However, the expression level, biological roles and underlying mechanism of miR‑493 in tongue squamous cell carcinoma (TSCC) remain to be elucidated.Methods: RT-qPCR was utilized for the determination of miR-493 expression in TSCC tissues and cell lines. The influence of miR-493 overexpression on TSCC cell proliferation, apoptosis, migration, invasion in vitro and tumor growth in vivo were explored via MTT assay, flow cytometry analysis, cell migration and invasion assays, and xenograft tumors in nude mice, respectively. Bioinformatics analysis, luciferase reporter assays, RT-qPCR and Western blotting were performed to clarify the potential mechanisms involved in the action of miR-493 in TSCC cells.Results: miR-493 was significantly downregulated in TSCC tissues and cell lines. Decreased miR-493 expression was notably correlated with tumor differentiation, depth of invasion and TNM stage. Additionally, patients with TSCC having low miR-493 expression showed lower overall survival rate. Functionally, miR-493 upregulation inhibited TSCC cell proliferation, migration, invasion in vitro; induced cell apoptosis; and decreased the tumor growth in vivo. Bioinformatics analysis followed by luciferase reporter assays also demonstrated that miR-493 directly bound to the 3ʹ-untranslated region of high-mobility group AT-hook 2 (HMGA2) in TSCC cells, and therefore reduced HMGA2 expression at the mRNA and protein level. Furthermore, HMGA2 was overexpressed in TSCC tissues and inversely correlated with miR-493. Moreover, silenced HMGA2 expression simulated the tumor-suppressing roles of miR-493 overexpression on TSCC cells. HMGA2 overexpression eliminated the inhibitory roles of miR-493 overexpression on TSCC cells.Conclusion: These observations demonstrated that miR-493 is a tumor suppressor inhibited the oncogenicity of TSCC cells by directly targeting HMGA2. These results provide sufficient evidence for the miR-493/HMGA2 axis as a novel therapeutic target for the treatment of patients with TSCC in the future.Keywords: tongue squamous cell carcinoma, microRNA-493, high-mobility group AT-hook 2, gene therapy